Neurobiological and neuropsychological disturbance in EDS - Westerman, Matt; Kafkas, Alex; Parry-Jones, Adrian; Strong, Samantha; Retzler, Chris; Hallam, Glyn (Frontiers in Neurology, 2025)
Ehlers-Danlos Syndrome (EDS) is a collection of connective tissue disorders, defined by genetic defects in collagen and extracellular matrix proteins that lead to joint hypermobility, skin fragility, and vascular complications. However, recent studies point to a broader impact, revealing how EDS has both neurological and psychological effects. This review explores these neurological and neuropsychological dimensions of EDS across its 13 subtypes, drawing together evidence on brain structure changes such as Chiari malformations and craniocervical instability, alongside small fibre neuropathy, blood–brain barrier vulnerabilities, and cerebrovascular risks, particularly prevalent in the vascular EDS subtype. The review will also explore how these physical disruptions may act upon mental health, fueling anxiety, mood instability, and cognitive challenges. Mechanisms such as neuroinflammation, altered interoception, and chronic pain may contribute to these effects and drive emotional dysregulation. By reviewing clinical observations, neuroimaging findings, and emerging theories, this paper highlights the importance of understanding the involvement of the brain in EDS. The review highlights the need for a shift in approach to EDS, and an integrated effort across neurology, psychiatry, and genetics to better support those living EDS.